Golden ratio, golden triangle and golden spiral of hilt keris designed by using extended cubic B-Spline and λµ-B-Spline / Nur Izzati Mahyudin and Aidatul Anisa Saiful Zamri - Mahyudin, Nur Izzati; Saiful Zamri, Aidatul Anisa (2019)
Keris is known as something precious to Malay race in back then and even today. Hilt Keris have numerous design, so this research are utilized to help in finding the best design. Golden ratio, golden spiral and golden triangle are used to find the best design of hilt Keris based on its best value which are 1.6180339877. Extended cubic B-spline and λµ -B-spline are used to interpolate the design of hilt Keris. In extended cubic B- spline, different value of parameter, λ are used while in λµ -B-spline, another parameter is added which is p, and these two parameter are changed in order to form various design of hilt Keris. The purpose of this research are to design two- dimensional hilt Keris using extended cubic B-spline and λµ -B-spline, to implement golden ratio, golden triangle and golden spiral in the design of hilt Keris obtained from the B-spline methods and compare the result to come by which method that give the best design of hilt Keris. In this research, the parameter value, λ = 3 gives the best design since the value of golden ratio and golden spiral are approaching to the value of 1.6180339877 compared to the others.